OP0062 Assessment of biotherapies' efficacy in blau syndrome: data from an international retrospective cohort of 23 cases. (15th June 2017) - Fogel, O; Cantagrel, A; Ikeda, K; Sève, P; Hachulla, E; Cimaz, R; Sfriso, P; Punzi, L; Pajot, C; Grouteau, E; Tellier, S; Galeotti, C; et al.
Abstract : Background: Blau Syndrome (BS) is a rare autosomal dominant inflammatory disease characterized by early-onset granulomatous arthritis, dermatitis and recurrent uveitis (1). Mutations in the nucleotide-binding domain (NBD) of CARD15/NOD2 gene (mainly R334W, R334Q and L469F) have been identified in Blau syndrome (2). Despite advances in BS knowledge, patients' functional prognosis remains uncertain, BS potentially leading to visual impairment or joint deformities. Optimal treatments have not been determinated yet. Objectives: To assess the efficacy of several biologic agents in this affection Methods: We conduct an observational, international, retrospective cohort of BS collecting clinical, biological and histological data. Results: Among the twenty-three patients included in the cohort, 14 patients were treated by one or several lines of biologic agents, mostly by TNF blockers (80%), IL1 blockers (16%) or treatment targeting CTLA-4 (4%). Fifty-seven percent of patients achieved remission after almost two lines of treatment (1.75 lines; [0.8–2.7]). Association with csDMARDs did not significantly improved response to biologics. Considering the 3 mains symptoms independently, TNF blockers were associated with a better response in case of articular or skin features but less effective in case of ocular involvement, a clinical situation in which IL-1 targeting should be preferentially chosen. Conclusions: Biologic treatments appeared to be effective in BS but additional data prospectively collected are still needed in order to define their place in the therapeutic strategy in order to minimize functional consequences. References: Blau EB. Familial granulomatous arthritis, iritis, and rash. The Journal of pediatrics. 1985 Nov;107(5):689–93. PubMed PMID: 4056967. Epub 1985/11/01. eng. Miceli-Richard C, Lesage S, Rybojad M, Prieur AM, Manouvrier-Hanu S, Hafner R, et al. CARD15 mutations in Blau syndrome. Nature genetics. 2001 Sep;29(1):19–20. PubMed PMID: 11528384. Epub 2001/08/31. eng. Disclosure of Interest: None declared